Musique de joye. Proceedings of the International Symposium on the Renaissance Flute and Recorder Consort, Utrecht 2003 - Lasocki, David (Utrecht Stimu, 2005)
This substantial volume is an extended version of the proceedings of the 2003 Utrecht symposium, which was originally planned with the title 'From Paumann to Giustiniani c.1470?c.1630: the recorder consort in the 16th century'. Its scope, however, was widened to include the transverse flute consort, which co-existed with the recorder consort and had a largely similar repertory. The resultant volume will be required reading for a relatively small number of specialist wind-instrument organologists and makers of Renaissance-type flutes and recorders, as well as for scholars of Renaissance wind-music repertory and performance practice. It should be studied by all recorder and flute players with a serious interest in Renaissance music. They may find parts of it heavy going or rather technical, but the reward for perseverance will be a far greater understanding of how Renaissance polyphony may be played, of the pitches of the most appropriate instruments for consorts, and of how, following the precepts of Ganassi and others, to perform in the manner of singers for whom much of the recorder and flute repertory was originally intended.The book is in five main sections, addressing the topics of consorts; instruments; performance and repertory (including Peter van Heyghen's 100-page monograph on 'The recorder consort in the 16th century', which acts as a centre-piece to the whole volume); music in art in the studiolo and Kunstkammer of the Renaissance; and the lives of players and makers of the flute and recorder. The useful appendices include Adrian Brown's list of 196 surviving Renaissance recorders, and Lasocki's compendious list of inventories and purchases of flutes, recorders, flageolets and tabor pipes 1388-1630 (already available online at www.music.indiana.edu/reference/bibliographies/inventoriesto1630.pdf).
Keywords: Festival Oude Muziek Utrecht (Netherlands); Renaissance (1400-1600); Flute; Recorder; Organology; Historically informed performance